Optimasi Kalsium Silikat (CaSiO3) dari Batu Kapur Menggunakan Metode Response Surface Methodology (RSM) - Miftachul Wijaya; Muhammad Nizammudin Baihaqi; Ni Ketut Sari (G-Tech: Jurnal Teknologi Terapan, 2024)
Calcium silicate is a chemical compound with the formula CaSiO₃ that is often used in various industrial fields. Calcium silicate is produced through several methods, one of which is the solid-state reaction method. CaO is obtained by calcining limestone to remove CO₂ compounds for 4 hours at a temperature of 900°C. The production of calcium silicate is carried out using the solid-state reaction method with variables set at different mixing ratios of CaO and SiO₂ (1:0.5; 1:0.75; 1:1; 1:1.25; and 1:1.5) and reaction temperatures to form calcium silicate (1000°C, 1050°C, 1100°C, 1150°C, and 1200°C). This research aims to determine the best CaO to SiO₂ ratio produced in the study using the solid-state reaction method optimized through Response Surface Methodology (RSM). The optimization results with RSM indicate that the optimum point in the experiment is at a temperature of 1050°C with a mixing ratio of 1:0.5